Feature of Nonlinear Electromagnetic Properties and Local Atomic Structure of Metals in Two Systems of Nanocomposites Cox(MgF2)100−x and (CoFeZr)x(MgF2)100−x - Evelina Pavlovna Domashevskaya; Sergey Alexandrovich Ivkov; Elena Alexandrovna Ganshina; Lyubov Vladimirovna Guda; Valeriy Grigoryevich Vlasenko; Alexander Victorovich Sitnikov (Nanomaterials)
Based on modern concepts of the nonlinear percolation mechanisms of electrical and magnetic properties in granular metal–dielectric nanocomposites, the authors present for the first time a comparative analysis of their own results of a comprehensive study of nonlinear electromagnetic properties in two nanocomposite systems: metal–dielectric Cox(MgF2)100−x and alloy–dielectric (CoFeZr)x(MgF2)100−x, obtained by ion-beam sputtering of composite targets in a wide range of different compositions. For the first time, the features of the influence of atomic composition and structural-phase transitions on nonlinear magnetoresistive, magnetic, and magneto-optical properties in two systems are presented in comparison, one of which, Cox(MgF2)100−x, showed soft magnetic properties, and the second, (CoFeZr)x(MgF2)100−x, hard magnetic properties, during the transition from the superparamagnetic to the ferromagnetic state. Moreover, for the first time, the concentration dependences of the oscillating fine structure of XANES K-absorption edges of Co atoms in the first system and Co and Fe atoms in the second system are presented, which undergo changes at the percolation thresholds in each of the two systems and thus confirm the nonlinear nature of the electromagnetic properties changes in each of the two systems at the atomic level.